2021
DOI: 10.3389/fpsyt.2021.780542
|View full text |Cite
|
Sign up to set email alerts
|

Surveying 80 Years of Psychodrama Research: A Scientometric Review

Abstract: Almost a century after Jacob Levy Moreno pioneered the group practice of psychodrama, research in this area has flourished to include different sub-fields of study and psychodramatic intervention for various psychological conditions. By making use of scientometric analysis, particularly document citation analysis and keyword analysis, this study maps out dominant research domains in psychodrama since its inception. From these findings, projections of future research trends and an evaluation of psychodrama rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 109 publications
1
7
0
Order By: Relevance
“…The following documents in order of citation burst strength are authored by Grove et al [ 42 ] (strength of burst = 9.462; burst duration = 2) and Iakoucheva et al [ 43 ] (strength of burst = 8.080; burst duration = 2). A partial list of the 20 documents with the highest citation burstness and their metrics are summarised in Table 2 , in accordance with Carollo et al [ 33 ], Gaggero et al [ 39 ], Lim et al [ 44 ]. It should also be noted that documents with their “Burst End” year marked as 2022 could be considered as still experiencing their citation bursts, implying that several of these references may continue to be highly cited even beyond 2022.…”
Section: Resultssupporting
confidence: 61%
“…The following documents in order of citation burst strength are authored by Grove et al [ 42 ] (strength of burst = 9.462; burst duration = 2) and Iakoucheva et al [ 43 ] (strength of burst = 8.080; burst duration = 2). A partial list of the 20 documents with the highest citation burstness and their metrics are summarised in Table 2 , in accordance with Carollo et al [ 33 ], Gaggero et al [ 39 ], Lim et al [ 44 ]. It should also be noted that documents with their “Burst End” year marked as 2022 could be considered as still experiencing their citation bursts, implying that several of these references may continue to be highly cited even beyond 2022.…”
Section: Resultssupporting
confidence: 61%
“…The two macro-areas were then called "Methods of wine making" and "Consumers' attitudes and preferences towards wine", respectively (see Figure 2). Furthermore, according to CiteSpace's Narrative Summary function (Chen and Song, 2019;Liu et al, 2020;Lim et al, 2021;Gao et al, 2021), clusters #0 -"Non Conventional Yeasts"and #1 -"Buyers' Attitudes"were identified as the meaningful ones in the network.…”
Section: Resultsmentioning
confidence: 99%
“…The use of the scientometric approach is gaining momentum in recent years and the method proved its efficacy in reviewing literature topics belonging to the fields of neurobiology, clinical psychology, developmental psychology (Carollo et al. , 2021a, b, c; Lim et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…DCA was computed and thematic clusters were identified. Below, we present the contributions of major thematic clusters identified by the Narrative Summary CiteSpace’s function (as in Liu et al, 2020 ; Lim et al, 2021 ). We discuss major clusters in chronological order based on the average year in which their documents were published.…”
Section: Discussionmentioning
confidence: 99%